Implementation of Project-Based Learning (PjBL) Assisted by Geogebra Application to Improve Students’ Spatial Abilities - Mulyaningrum Lestari; Wahyuning Widyastuti; Eka Nurul Amalia (Absis: Mathematics Education Journal, 2026)
The purpose of this study was to determine whether the implementation of the Geogebra-assisted Project Based Learning (PjBL) model has an impact on improving students' spatial abilities or not. Quantitative method with experiments was used in this study. The sample used was class B and C students of Mathematics Education IAIN Kudus class of 2022/2023 who were selected through cluster random sampling techniques. To determine the level of effectiveness, pretest and posttest instruments were given to students. Before the instrument was given, content, construct, and item tests were carried out. Based on the content validation test given by two experts, a V-Aiken score of 0.93 was obtained, which was categorized as very valid. Furthermore, item tests were carried out, which included item validity tests, discrimination power, level of difficulty, and reliability. Based on the analysis of the item test, it was stated that all questions could be used. The effectiveness test was carried out using N-Gain, and an average score of 3.896 was obtained, categorized as moderate. From these calculations, it is concluded that PjBL learning models assisted by the Geogebra application have a positive impact on improving students' spatial abilities.